Diseases during pregnancy in a large unselected South American sample - Santos, María Rita (2022)
Objective: Our aim was to describe the prevalence of diseases during pregnancy and the association between fetal exposure to the most frequent maternal diseases and the risk of preterm (PTB) and/or small for gestational age (SGA) newborns in an unselected sample of women who gave birth in South American countries. Methods: We conducted a descriptive, cross-sectional study including 56,232 mothers of non-malformed infants born between 2002 and 2016, using data from the Latin American Collaborative Study of Congenital Malformations (ECLAMC). Diseases with higher-than-expected PTB/SGA frequencies were identified. Odds ratios of confounding variables for diseases and birth outcomes were calculated with a multivariable logistic regression. Results: Of the 14 most reported diseases, hypertension, genitourinary infection, epilepsy, hypothyroidism, diabetes, and HIV/AIDS showed higher PTB and/or SGA frequencies. Advanced and low maternal age, previous fetal loss, low socioeconomic level, and African-American ancestry were associated with PTB, while advanced maternal age, primigravidity, previous fetal loss, low socioeconomic level, and African-American ancestry were associated with SGA. After adjusting for the associated variables, the identified illnesses maintained their association with PTB and all, except epilepsy, with SGA. Conclusion: The description of an unselected population of mothers allowed identifying the most frequent diseases occurring during gestation and their impact on pregnancy outcomes. Six diseases were associated with PTB and two with SGA newborns. To the best of our knowledge, there are no similar reports about women not intentionally selected by specific diseases during pregnancy in South American populations.